Effect of discharge instructions on readmission of hospitalised patients with heart failure: do all of the Joint Commission on Accreditation of Healthcare Organizations heart failure core measures reflect better care?. Issue 6 (1st December 2006) - VanSuch, Monica; Naessens, James M; Stroebel, Robert J; Huddleston, Jeanne M; Williams, Arthur R
Abstract : Background: Most nationally standardised quality measures use widely accepted evidence-based processes as their foundation, but the discharge instruction component of the United States standards of Joint Commission on Accreditation of Healthcare Organizations heart failure core measure appears to be based on expert opinion alone. Objective: To determine whether documentation of compliance with any or all of the six required discharge instructions is correlated with readmissions to hospital or mortality. Research design: A retrospective study at a single tertiary care hospital was conducted on randomly sampled patients hospitalised for heart failure from July 2002 to September 2003. Participants: Applying the Joint Commission on Accreditation of Healthcare Organizations criteria, 782 of 1121 patients were found eligible to receive discharge instructions. Eligibility was determined by age, principal diagnosis codes and discharge status codes. Measures: The primary outcome measures are time to death and time to readmission for heart failure or readmission for any cause and time to death. Results: In all, 68% of patients received all instructions, whereas 6% received no instructions. Patients who received all instructions were significantly less likely to be readmitted for any cause (p = 0.003) and for heart failure (p = 0.035) than those who missed at least one type of instruction. Documentation of discharge instructions is correlated with reduced readmission rates. However, there was no association between documentation of discharge instructions and mortality (p = 0.521). Conclusions: Including discharge instructions among other evidence-based heart failure core measures appears justified.